Nursing students' perceptions towards being taught the fundamentals of care by clinical nurses within a simulated learning environment: A qualitative study. (March 2019) - Lillekroken, Daniela
Abstract: Research in nursing education demonstrates that the fundamentals of care are paid less attention in this field resulting in negative consequences for students' learning outcomes. The aim of this qualitative study was to explore nursing students' perceptions towards being taught the fundamentals of care by clinical nurses within a simulated learning environment. The study has a qualitative explorative design. Data was collected through participant observation and focus group interviews and analysed using qualitative content analysis. The analysis revealed two main categories indicating how the students gained knowledge in the research setting: 'Getting the best of both worlds', and 'Having it in many ways'. The findings are discussed against Vygotsky's theory of cognitive development suggesting that the students were content with being taught the fundamentals of care by clinical nurses within an simulated learning environment.